Between Religious Controversy and Commodification: A Study of Dauroh Poligami Indonesia - Trie Yunita Sari (Indonesian Center for Religion and Society Studies (InTReSt), 2023)
While polygamy is the consensus of ulama (Islamic clerics) and is allowed by marriage law 1974, polygamy is still a highly controversial religious-based practice that continuously triggered pros and cons in Indonesian society. Polygamy is considered a form of gender inequality and violence against women. Many movements aspire to eliminate all forms of gender inequality and violence against women, including the campaign of 16- Days Anti Violence against Women initiated by Komnas Perempuan and feminist collectives.However, during the campaign in 2017, a recent pro-polygamous organization named Dauroh Poligami Indonesia came to the public to promote polygamy seminars. The emergence of Dauroh Poligami Indonesiais much criticized on account of commercialization and gender violence. Against this backdrop, this article seeks to understand the emergence of pro-polygamy collectives like Dauroh Poligami Indonesia. To fill the gap in the discourse about polygamy, this article shall presentcredible voices of women's pro-polygamous marriage. Why are there women still supporting polygamy, despite concerns about sexual, psychic, and economic violence to women affected by polygamy. This qualitative study employed extensive observation of pro-polygamous movement’s narratives both on social media and private whatsapp group, interviews, and participative observation from late 2017 to July 2022. By drawing on the commodification and self-autonomy framework, this study finds that the emergence of Dauroh Poligami Indonesia is not solely to gain profit using religious-based practice but also to contest Islamic ideology among Islamic denominations and liberal women rights defenders in Indonesia.